Lembranças, esquecimentos e representações: as construções de memórias de Maria Firmina dos Reis (1822-2022) - Mendonça, Renata Toledo Piza de (2023)
This thesis seeks to discuss how writer Maria Firmina dos Reis (1822/25-1917) from Maranhão is remembered and celebrated by different social groups in the 20th century and in the first decades of the 21st century. For this purpose, representations produced about her between 1975 and 2022 are investigated, analyzing how they manifest themselves in the celebrations of important dates in her biography. This analysis seeks to identify and reflect on the permanencies and transformations in the construction processes of memories and forgetfulness around her life and work. Such examination takes place in articulation with the concepts of Freedom and Oppression worked by the author herself in book “Úrsula” (1859/1860). In this sense, the research involves the analysis of sources produced and/or made public in ephemeris of the biography of Maria Firmina dos Reis, as it is understood throughout the study that commemorative dates are like time frames capable of functioning as guides, which can lead the observer to records of the daily life of social groups, the ways and interests of their subjects and fragments of their individual and collective memories. In this way, books, materials published in the press, images and celebratory acts produced in 1975, on the occasion of the celebrations for the 150th anniversary of the author's birth, are analyzed; as well as those produced in 1988, the centenary of Abolition, on the occasion of the second posthumous edition of book “Úrsula”; in 2017, due to the centenary of her death; in 2020 and 2022, respectively, on the 198th and 200th anniversary of her birth. This thesis seeks to contribute a new perspective to the historiography of Firmina by proposing the reconstitution and analysis of memories of Maria Firmina dos Reis, approaching both the process of construction of memories and the active process of construction of forgetfulness about such woman from Maranhão. At the same time, it seeks to identify the forces that move groups and subjects that produce the representations and documents analyzed, their social practices, the interpretations they made – and still make – of Maria Firmina dos Reis and their appropriations of “Úrsula”, apprehended in the dialogue with the sources